Atomically Altered Hematite for Highly Efficient Perovskite Tandem Water‐Splitting Devices. Issue 11 (12th May 2017) - Gurudayal,; John, Rohit Abraham; Boix, Pablo P.; Yi, Chenyi; Shi, Chen; Scott, M. C.; Veldhuis, Sjoerd A.; Minor, Andrew M.; Zakeeruddin, Shaik M.; Wong, Lydia Helena; Grätzel, Michael; Mathews, Nripan
Abstract: Photoelectrochemical (PEC) cells are attractive for storing solar energy in chemical bonds through cleaving of water into oxygen and hydrogen. Although hematite (α‐Fe2 O3 ) is a promising photoanode material owing to its chemical stability, suitable band gap, low cost, and environmental friendliness, its performance is limited by short carrier lifetimes, poor conductivity, and sluggish kinetics leading to low (solar‐to‐hydrogen) STH efficiency. Herein, we combine solution‐based hydrothermal growth and a post‐growth surface exposure through atomic layer deposition (ALD) to show a dramatic enhancement of the efficiency for water photolysis. These modified photoanodes show a high photocurrent of 3.12 mA cm −2 at 1.23 V versus RHE, (>5 times higher than Fe2 O3 ) and a plateau photocurrent of 4.5 mA cm −2 at 1.5 V versus RHE. We demonstrate that these photoanodes in tandem with a CH3 NH3 PbI3 perovskite solar cell achieves overall unassisted water splitting with an STH conversion efficiency of 3.4 %, constituting a new benchmark for hematite‐based tandem systems. Abstract : ALD makes the difference : We combine solution‐based hydrothermal growth and a post‐growth surface exposure through atomic layer deposition (ALD) to show a dramatic enhancement of the efficiency for water photolysis. The photoanodes in tandem with a CH3 NH3 PbI3 perovskite solar cell achieves overall unassisted water splitting with a solar‐to‐hydrogen conversion efficiency of 3.4 %.